Pengaruh Strategi Pembelajaran Inkuiri terhadap Self-Regulated Learning Siswa pada Mata Pelajaran PAI - Jelita Jelita; Revi Aulia Putri; Gusmaneli Gusmaneli (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study was motivated by the low level of students’ self-regulated learning in Islamic Religious Education (IRE) classes, where the learning process tends to remain one-sided and teacher-centered. The purpose of this study was to analyze the effect of inquiry-based learning strategies on students’ self-regulated learning in IRE classes. The research method used was quantitative with a quasi-experimental design. Data were collected through a self-regulated learning questionnaire and observations of learning activities, which were then analyzed using a t-test to determine the significance of differences between the experimental and control classes. The results indicate that the implementation of inquiry-based learning strategies significantly enhances students’ self-regulated learning compared to conventional methods, as students become more active in planning, monitoring, and evaluating their own learning processes. The implications of this study are that inquiry strategies can serve as an effective alternative learning model for Islamic Education teachers to foster students’ character traits of independence, critical thinking, and responsibility toward their spiritual and academic achievements.